The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1039/c2cc30429e
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed direct phosphonation of azoles with dialkyl phosphites

Abstract: The first Pd-catalyzed direct phosphonation of azoles with dialkyl phosphites has been achieved without addition of base or acid. This method involves the oxidative cleavage of C-H and P(O)-H bonds and represents an atom-efficiency alternative to the classical phosphonation of Ar-X. A Pd(II)/Pd(IV) mechanism has been studied and proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(49 citation statements)
references
References 52 publications
1
45
0
3
Order By: Relevance
“…), a transition metal aromatic C-H activation recently emerged as a viable alternative for C-C and C-heteroatom bonds formation [118][119][120][121]. Scheme 17 depicts the first Pd-catalyzed direct phosphonylation of non-functionalized azoles with diethyl H-phosphonate (which occurs without the addition of acid or base) [122]. The method consists of an oxidative cleavage of the C-H and P-H bonds and proceeds probably via a Pd(II)/Pd(IV) catalytic cycle.…”
Section: Pd-catalyzed Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…), a transition metal aromatic C-H activation recently emerged as a viable alternative for C-C and C-heteroatom bonds formation [118][119][120][121]. Scheme 17 depicts the first Pd-catalyzed direct phosphonylation of non-functionalized azoles with diethyl H-phosphonate (which occurs without the addition of acid or base) [122]. The method consists of an oxidative cleavage of the C-H and P-H bonds and proceeds probably via a Pd(II)/Pd(IV) catalytic cycle.…”
Section: Pd-catalyzed Reactionsmentioning
confidence: 99%
“…An analogous catalyst system was used for direct phosphonylation (C-H activation) of coumarins with dialkyl H-phosphonates to produce the corresponding 3-phosphonylated coumarin derivatives in a highly regioselective manner, with moderate to good yields [123]. Although Pd(II)-catalyzed reactions typically proceed via a Pd(II)/Pd(0) catalytic cycle (Scheme 17), a Pd(IV) species [124] was postulated as an intermediate [122,123].…”
Section: Pd-catalyzed Reactionsmentioning
confidence: 99%
“…1 In the past few years, several attempts have been made to develop efficient methods for the functionalization of these types of heterocycles. [2][3][4][5][6][7] Among these methods, direct halogenation has received much attention from organic chemists, because the corresponding halide can be converted to other functional groups by transition metal-catalysed cross-coupling reactions. In 2009, Daugulis reported the preparation of 2-bromo-and 2-chloro-1,3-azoles by direct halogenation using LiOtBu as a base; 8 however, to the best of our knowledge, strong bases, such as nBuLi together with MgBr 2 ,or TMPLi (TMP = 2,2,6, together with CdCl 2 (TMEDA), or ZnCl 2 (TMEDA) (TMEDA = N,N,N 0 ,N 0 -tetramethylethylenediamine) are required for the direct iodination of the 2-position C-H in 1,3-azoles (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Li's groups reported that the ligand could be employed to enhance the efficiency of Pd-catalyzed phosphonation reaction. 6,8 The yield of 3a significantly increased from 16% to 52% after introducing Bpy (2,2 0 -bipyridine) as a ligand (Table 1, entry 2). Other ligands such as TMEDA (N,N,N 0 ,N 0 -tetramethylethane diamine), L-proline and Phen (1,10-phenanthroline) were also examined, and Phen proved to be the best one to give 3a in 65% yield (Table 1, entries 3-5).…”
mentioning
confidence: 97%
“…The monocationic palladium complex II was formed by nucleophilic coordination of the phosphite to Pd II , which was detected by Li and Wu's groups. 6,8 Then, the more nucleophilic C-5 position of 3-methyl-6-phenylimidazo[2, 1-b]thiazole 1a is attacked by the Pd complex II to generate another palladium complex III. Subsequently, the oxidation/dehydrogenation process takes place in the presence of K 2 S 2 O 8 , affording the Pd IV species IV.…”
mentioning
confidence: 99%